THEORETICAL AND PRACTICAL ISSUES OF BIOLOGICAL OXIDATION OF HYDROCARBONS BY MICROORGANISMS - A. V. Bryanskaya; Yu. E. Uvarova; N. M. Slynko; E. A. Demidov; A. S. Rozanov; S. E. Peltek (Вавиловский журнал генетики и селекции)
The paper deals with the theoretical issues of biological oxidation of oil hydrocarbons from alkanes to polycyclic aromatics. We analyze the mechanisms of biochemical processes of decomposition of oil components and provide an overview of data from common databases. Studies of microbial communities of natural oil seeps in the Uzon caldera are described in detail. It is the first study of ecophysiological characteristics of oil-degrading microorganisms isolated from thermal oil seeps of the caldera.